2018
DOI: 10.1111/pde.13607
|View full text |Cite
|
Sign up to set email alerts
|

Trimethoprim‐sulfamethoxazole‐induced drug reaction with eosinophilia and systemic symptoms in a child with congenital renal disease

Abstract: We present a special case of an 8-year-old girl diagnosed with severe drug reaction with eosinophilia and systemic symptoms due to trimethoprim-sulfamethoxazole for urinary tract infection prophylaxis for congenital vesicoureteral reflux. The patient is believed to have developed drug reaction with eosinophilia and systemic symptoms because of her underlying renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Newell et al found phenytoin, carbamazepine, and phenobarbital to be the most common culprits, while other pediatric DRESS series confirmed lamotrigine and phenytoin, respectively, as the most common etiologies . In the pediatric literature, antibiotics are being increasingly reported as the primary etiology with vancomycin, amoxicillin‐clavulanic acid, and trimethoprim‐sulfamethoxazole most commonly reported …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Newell et al found phenytoin, carbamazepine, and phenobarbital to be the most common culprits, while other pediatric DRESS series confirmed lamotrigine and phenytoin, respectively, as the most common etiologies . In the pediatric literature, antibiotics are being increasingly reported as the primary etiology with vancomycin, amoxicillin‐clavulanic acid, and trimethoprim‐sulfamethoxazole most commonly reported …”
Section: Discussionmentioning
confidence: 99%
“…6,9,34 In the pediatric literature, antibiotics are being increasingly reported as the primary etiology with vancomycin, amoxicillin-clavulanic acid, and trimethoprim-sulfamethoxazole most commonly reported. [6][7][8][9][12][13][14][15][16][17][18][19]21 Patients developed symptoms and presented to physicians at 4 and 5 weeks, respectively, after the inciting medication. Previous series reported an earlier onset of antibiotic-induced pediatric DRESS with an average time to symptoms of approximately 6-11 days after antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen case reports, six case series, and four retrospective cohort studies, published between 1984 and 2022, with a total of 140 patients, from preterm newborn neonates to adolescents, were included (Table 1) . Most of the studies were conducted in infants (n = 6) [20][21][22][23][24][25][26] and children (n = 13) [27][28][29][30][31][32][33][34][35][36][37][38][39]. In addition, one study reported findings from either preterm newborn neonates [18] or term or postterm neonates [19], and four studies included adolescents [36,38,40,41] (of note, Novelli et al [36] and Scheffner et al [38] reported findings from both children and adolescents).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%